How permeable is the edge of the Arctic vortex: Model studies of winter 1999-2000 - Steinhorst, H.-M.; Konopka, Paul; Günther, G.; Müller, R. (Journal of Geophysical Research: Atmospheres, 2005)
The edge of the Arctic vortex constitutes a strong barrier to transport; however, the extent of isolation of the vortex air as a function of altitude and season is relatively poorly quantified. In this study, by examining the transport of midlatitude air parcels across the vortex edge into the vortex, we analyze the permeability of the vortex edge. With the three-dimensional version of CLaMS (Chemical Lagrangian Model of the Stratosphere) we explore the dilution of the vortex air due to mixing in winter 1999-2000. An artificial, passive tracer was initialized on 1 December 1999 inside the polar vortex with a value of 100% and with a value of zero outside the polar vortex. Using several different definitions of the vortex edge, the resulting intrusions of midlatitude air into the vortex show the same mean features. This demonstrates that the diagnosed dilution does not strongly depend on the details of the definition of the vortex edge. At about the end of March 2000, the vertical structure of the vortex consisted of well-isolated, pure vortex layers around 500 K and 750 K, with some more diluted layers in between and at the vortex bottom. The influence of wave activity on the evolution of the intrusion layers is studied. The divergence of the Eliassen-Palm flux shows such a high variability during the whole period that it is not possible to assess a direct causality of certain intrusion layers and some specific patterns. Some characteristics of the vortex edge, in particular the shape of the gradient of potential vorticity (PV), can influence the dilution of the vortex. In cases without a distinct maximum in the PV gradient, the defined "vortex edge'' may vary substantially from day to day. The comparison of some properties of the vortex (wind speed, PV field, area of the vortex, the maximum of the PV gradient) of undisturbed versus diluted layers and the variation in time of the intrusions were analyzed. All observed intrusions begin in conditions of weak PV gradient, indicating that the value of the maximum of ...